Lithium-rich positive electrode material, preparation method thereof and lithium ion battery

By synergistically regulating gradient doping and surface nanocomposite structures, the voltage decay and cycle stability problems of lithium-rich cathode materials were solved, achieving long cycle performance and low voltage decay at high voltage.

CN121394334APending Publication Date: 2026-01-23ANHUI SCI & TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511426277.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing lithium-rich cathode materials have shortcomings in terms of high capacity and long cycle performance, especially the voltage decay problem, and existing surface treatment methods are not effective.

Method used

By employing the synergistic regulation of elemental gradient doping and surface nanocomposite structure, a stable multi-level modified surface is constructed. The material structure transformation and interfacial side reactions are suppressed by the protective layer of gradient doped elements, forming a spinel nanocomposite structure to stabilize lattice oxygen.

Benefits of technology

It achieves long cycle performance and low voltage decay characteristics under high voltage, with a charging cut-off voltage ≥4.3V, a capacity retention rate ≥90% when the number of cycles ≥100, and a voltage decay value per cycle <1.5mV.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121394334A_ABST
    Figure CN121394334A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-rich positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of lithium ion batteries. The chemical formula of the lithium-rich positive electrode material is Li < 1 + x > TM < 1-x-y > DyO2 (TM is at least two of Ni, Co and Mn, D is at least two of Mg, Ti, Al, Zr, Nb and Ta, 0 lt; xlt; 0 < y < = 0.06), material particles are a spinel phase and a bulk phase in sequence from outside to inside, the concentration of TM is gradually increased from outside to inside, and the concentration of N is gradually reduced from outside to inside. The preparation method adopts a liquid-phase mechanical fusion coating technology to realize gradient doping of doping elements, and combines high-temperature calcination to obtain a target product. The lithium-rich positive electrode material disclosed by the invention is used as a positive electrode of a lithium ion battery, a stable multi-stage modified surface can be constructed through element gradient doping and surface nano-composite structure coordinated regulation and control, material structure transformation and interface side reaction are inhibited, high voltage greater than or equal to 4.3 V is realized, the capacity retention rate greater than or equal to 90% of cycles greater than or equal to 100 times is realized, and voltage attenuation lt of each circle is realized; and the material has excellent performance of 1.5 mV, and is suitable for the fields of power batteries, energy storage and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lithium ion batteries, and more particularly to a lithium-rich cathode material, a preparation method thereof and a lithium ion battery. BACKGROUND

[0002] Lithium ion batteries have high energy density, long life, low cost and no memory effect. In the fields of electric tools, electric vehicles, energy storage and others, lithium ion batteries have become the most competitive candidate product, among which electric vehicles and energy storage have become the largest potential market for lithium ion battery in the future. At present, the commercial lithium ion battery cathode material is mainly lithium cobaltate, lithium manganate and nickel-cobalt-manganese ternary material, and lithium iron phosphate, among which lithium cobaltate accounts for most of the small lithium ion battery cathode material market, but due to its high price, low capacity, poor safety and toxicity, it cannot be used as a power lithium ion battery cathode material. Although the nickel-cobalt-manganese ternary material can be used as a power lithium ion battery cathode material, its limited capacity restricts the cruising range of electric vehicles. Lithium iron phosphate has good safety, but its theoretical capacity is only 170 mAh / g, and it cannot be used as a high cruising range electric vehicle battery cathode material. Therefore, researching new high energy density lithium ion cathode materials to improve the cruising range is the main method to solve the lack of competitiveness of electric vehicles.

[0003] In order to solve these problems, people have carried out a lot of research on the optimization and design of new high-voltage and high-capacity cathode materials. In the research of new cathode materials, especially lithium-rich cathode materials (LLOs, xLi2MnO3·(1-x)LiTMO2 (TM=Ni, Mn, Co, etc.), since the first discovery, it has attracted widespread attention. Because LLOs has a high manganese content, it reduces the cost of the material, at the same time has a high capacity of ~ 300 mAh / g and a high average discharge voltage (> 3.5V, ) and exhibits a high energy density of > 1000 Wh / Kg. Due to these advantages, LLOs is considered to be one of the most promising next-generation lithium ion battery cathode materials. However, LLOs is faced with serious capacity fading and voltage decay problems, which seriously restricts the application of the material in actual batteries.

[0004] Studies have shown that the decline of the discharge voltage platform has a great relationship with the crystal structure transformation of the material during the charging and discharging process. This structure transformation usually starts from the surface of the cathode material particles and gradually extends to the interior of the material. For this reason, people have researched the methods of surface doping and coating to carry out surface treatment and protection. The usual treatment method is to form a surface protection layer by coating or doping other elements on the surface of the material. Since the structure and properties of the material surface itself have not changed fundamentally, the effect of these methods is not very obvious. SUMMARY

[0005] The purpose of the present application is to solve the problem that the lithium-rich positive electrode material in the prior art is difficult to balance high capacity, long cycle and low voltage decay, and to provide a lithium-rich positive electrode material, a preparation method thereof and a lithium ion battery, which realizes long cycle performance and low voltage decay characteristics at high voltage through synergistic regulation of element gradient doping and surface nano-composite structure, and constructs a stable multi-level modified surface to inhibit material structure transformation and interface side reaction.

[0006] To solve the above technical problems, one of the technical solutions adopted by the present application is to provide a lithium-rich positive electrode material, which has a chemical formula of Li 1+x TM 1-x-y D y O2, wherein TM is at least two of Ni, Co and Mn, providing the material with basic electrochemical activity; D is at least two of Mg, Ti, Al, Zr, Nb, Ta doping elements, used for gradient doping modification; 0 < x < 0.4, 0 < y ≤ 0.06, to balance the lithium-rich characteristics and the doping modification effect;

[0007] The lithium-rich positive electrode material is a single crystal particle or a spherical agglomerate particle, which has a spinel phase and a bulk phase from outside to inside, and the bulk phase has a "double crystal domain" characteristic of a layered phase.

[0008] In the lithium-rich positive electrode material, the concentration of TM gradually increases from outside to inside, and the concentration of the doping element D gradually decreases from outside to inside, forming a gradient protective layer to inhibit interface reaction and structure diffusion.

[0009] Preferably, the particle size of the lithium-rich positive electrode material is 2-20 μm; the thickness of the spinel phase is 1-20 nm, and the thickness of the bulk phase doping layer is ≥200 nm.

[0010] The lithium-rich positive electrode material of the present application forms a spinel nano-composite structure on the surface, which helps to stabilize the surface lattice oxygen of the material and inhibit the surface structure transformation. The doping elements of the material are distributed in a gradient concentration, which effectively prevents electrolyte erosion and delays further transformation of the material structure. The synergistic effect of this gradient doping and surface nano-composite structure enhances the high-voltage cycle stability and voltage decay resistance of the material. The charge cut-off voltage is ≥4.3 V; the capacity retention rate is ≥90% when the cycle number is ≥100 times, and the voltage decay value is <1.5 mV per cycle, meeting the application requirements of high-voltage long cycle.

[0011] The second technical solution adopted by the present application is to provide a preparation method of a lithium-rich positive electrode material, which comprises the following steps:

[0012] S1, according to the chemical formula of the lithium-rich positive electrode material, lithium-rich precursors, coating agents and dispersants are weighed and added into a mechanical fusion device, and protective gas is introduced for mechanical fusion coating to obtain a mixed slurry;

[0013] S2, solid-liquid separation is carried out on the mixed slurry, and the mixed slurry is washed with a dispersant or deionized water and dried to obtain a coated precursor;

[0014] S3, the coated precursor is uniformly mixed with a lithium source according to a molar ratio, and then subjected to high-temperature calcination in sections to obtain a target lithium-rich positive electrode material after cooling.

[0015] Preferably, the lithium-rich precursor is a Ni-Co-Mn-based carbonate or a Ni-Co-Mn-based hydroxide.

[0016] Preferably, the coating agent includes a powder coating agent and a hydrolyzable salt coating agent, wherein the powder coating agent is an oxide or a hydroxide, and the hydrolyzable salt coating agent is at least one of the following: tantalum ethoxide, tantalum pentachloride, niobium ethoxide, aluminum isopropylate, aluminum sec-butyrate, tetrabutyl titanate, titanium isopropoxide, and titanium tetrachloride.

[0017] Preferably, the oxide is at least one of the following: magnesium oxide, aluminum oxide, niobium pentoxide, and tantalum pentoxide, and the hydroxide is at least one of the following: magnesium hydroxide, aluminum hydroxide, and zirconium hydroxide.

[0018] Preferably, the dispersant is at least one of the following: water, methanol, ethanol, ethylene glycol, isopropyl alcohol, and polyvinyl alcohol solution.

[0019] Preferably, the lithium source is lithium carbonate or lithium hydroxide.

[0020] Preferably, the specific process of the high-temperature calcination in sections is as follows: first, the temperature is raised to 400-600 DEG C at a rate of 5-20 DEG C / min, and the precursor impurities are removed by calcination for 2-8 h to preliminarily form a doped structure; then, the temperature is raised to 800-1000 DEG C at a rate of 5-20 DEG C / min, and a spinel-layered phase composite structure is formed by calcination for 8-20 h to realize element gradient distribution; and the calcination atmosphere is oxygen or air to ensure the material crystallinity and electrochemical activity.

[0021] The third technical solution of the present application provides a lithium ion battery, which comprises the lithium-rich positive electrode material or the lithium-rich positive electrode material prepared by the preparation method of the lithium-rich positive electrode material.

[0022] Compared with the prior art, the present application has the following beneficial effects:

[0023] 1. The liquid-phase mechanical fusion coating technology is adopted, the coating agent is uniformly attached to the surface of the precursor under the action of the dispersant, the product has good consistency, and the granular material is not bonded, thereby solving the problems of poor uniformity and easy agglomeration in the traditional coating process.

[0024] 2. Gradient elemental doping forms a protective structure of "outer layer highly doped elements - inner layer highly active metals", which can effectively isolate electrolyte corrosion, suppress the structural transformation of the material surface to the bulk phase during charging and discharging, and reduce interfacial side reactions.

[0025] 3. The surface spinel phase possesses three-dimensional Li + The diffusion channel enhances ion transport dynamics; at the same time, the spinel structure stabilizes lattice oxygen, avoiding capacity decay and voltage drop caused by oxygen release, ultimately achieving synergistic performance of high voltage (≥4.3V), long cycling (capacity retention ≥90% after 100 cycles), and low decay (<1.5mV per cycle).

[0026] 4. The material has low cost (high Mn content) and the preparation process can be scaled up, making it suitable for power batteries and energy storage batteries, providing key cathode material support for high-range electric vehicles and high-capacity energy storage systems. Attached Figure Description

[0027] Figure 1 The image shows the XRD pattern of the lithium-rich cathode material modified by Ti-Al gradient doping in Example 1.

[0028] Figure 2 This is a SEM image of the lithium-rich cathode material modified by Ti-Al gradient doping in Example 1.

[0029] Figure 3 The image shows the HAADF-STEM image of the lithium-rich cathode material modified by Ti-Al gradient doping in Example 1.

[0030] Figure 4 This is a cross-sectional elemental EDS line scan analysis of the Ti-Al gradient doped lithium-rich cathode material from Example 1.

[0031] Figure 5 The first-cycle discharge curves are for the Ti-Al gradient doping modified and the unmodified lithium-rich cathode materials in Example 1 and the comparative example.

[0032] Figure 6 The cycling performance of the Ti-Al gradient doping modified and the unmodified lithium-rich cathode materials in Example 1 is compared with that of the comparative example.

[0033] Figure 7 The curves show the average voltage variation during cycling of the Ti-Al gradient doped modified cathode material in Example 1 and the unmodified lithium-rich cathode material in the comparative example. Detailed Implementation

[0034] The application is further described in connection with preferred embodiments, and the endpoints of the ranges of values disclosed herein and any values given herein are not to be construed as insulating from the exact ranges or values given, and these ranges or values are to be construed as covering values approximately ranging therefrom; for ranges of values, the endpoints of the ranges of values, the endpoints of the ranges of values and individual values therebetween, and individual values therebetween can be combined to form one or more new ranges of values, which are to be construed as being expressly disclosed herein.

[0035] Example 1

[0036] The present embodiment provides a lithium-rich positive material, which has a chemical formula of Li 1.13 Mn 0.514 Ni 0.254 Co 0.097 Ti 0.002 Al 0.003 O2.

[0037] The preparation method is as follows:

[0038] (1) Taking the Ti doping amount as 0.2% and the Al doping amount as 0.3% as the target, lithium-rich precursors (Mn 0.594 Ni 0.294 Co 0.112 CO3), tetrabutyl titanate (corresponding to the Ti doping amount), 10 nm Al2O3 (corresponding to the Al doping amount) and 200 ml of ethanol (dispersant) are weighed and added into a mechanical fusion device and nitrogen gas (protective gas) is introduced, and the device is operated at a rotation speed of 3000 r / min for 30 min to obtain a mixed slurry;

[0039] (2) The mixed slurry is subjected to solid-liquid separation, washed with ethanol for 3 times, and vacuum dried at 80℃ for 12 h to obtain a coated precursor;

[0040] (3) The coated precursor and lithium carbonate are added into a high-speed mixer at a molar ratio of 1:1.5 and mixed at a high speed for 1 h, and the mixed material is placed into a muffle furnace, and calcined at a rate of 5℃ / min to 400℃ for 8 h, then calcined at a rate of 5℃ / min to 800℃ and kept for 10 h, and cooled to room temperature to obtain a lithium-rich positive material Li 1.13 Mn 0.514 Ni 0.254 Co 0.097 Ti 0.002 Al 0.003 O2.

[0041] The XRD spectrum thereof is as shown in Figure 1As shown, the characteristic diffraction peaks of the lithium-rich cathode material are sharp and consistent with Li2MnO3 and LiTMO2, indicating that a lithium-rich cathode material with good crystallinity is prepared. The SEM image thereof is as shown in Figure 2 As shown, the lithium-rich cathode material is a spherical agglomerate particle assembled by nanoparticles, with a diameter of about 8 μm. The particle shows different contrasts inside and outside, as shown in Figure 3 As shown, there is a spinel phase layer with a thickness of about 2 μm on the surface, and the internal bulk phase is a layered lithium-rich cathode material matrix with a "twin domain" feature. The active metals (Ni, Co, Mn) are concentrated in the bulk phase to ensure capacity (the surface concentration is lower, and gradually increases towards the inside); the doping elements (Al, Ti) are concentrated in the surface layer to build a protective structure (the surface concentration is higher, and gradually decreases towards the inside), and the gradient doping depth is 3 μm, as shown in Figure 4 Thus, the synergistic performance of "high capacity and long cycle stability" of the material is achieved.

[0042] Electrochemical performance test:

[0043] The Ti-Al gradient-doped modified lithium-rich cathode material Li 1.13 Mn 0.514 Ni 0.254 Co 0.097 Ti 0.002 Al 0.003 O2 was prepared into a lithium ion battery cathode sheet in the following manner: the lithium-rich cathode material, conductive carbon and PVDF were mixed at a mass ratio of 8:1:1, and a certain amount of NMP was used as a solvent for sizing, the slurry was uniformly coated on an aluminum foil, vacuum dried at 100°C for 12 hours, and the cathode sheet with a diameter of 10 μm was prepared, and the sheet was pressed to the required thickness for standby. A CR2032 button half-cell was assembled in a glove box with a lithium metal sheet as a counter electrode, a Celgard 2400 film as a separator, and 1.2 mol / L LiPF6 / EC+EMC (volume ratio 3:7) as an electrolyte. The obtained battery was tested for electrochemical performance by a new battery test system tester, and the results showed that the first cycle discharge capacity of the button half-cell was 291.07 mAh / g at a voltage range of 2-4.8 V and a current density of 25 mA / g, and the corresponding first cycle coulombic efficiency was 89%, as shown in Figure 5 After 200 cycles at a voltage range of 2-4.6 V and a current density of 250 mA / g, the capacity retention rate was as high as 98.4%, as shown in Figure 6 and the average voltage did not decay Figure 7 , as shown. It is proved that the Ti-Al gradient-doped modified lithium-rich cathode material Li 1.13 Mn 0.514 Ni 0.254 Co 0.97 Ti 0.002 Al 0.03O2 shows high discharge specific capacity, excellent cycle stability and superior voltage retention effect.

[0044] Example 2

[0045] The present embodiment provides a lithium-rich positive electrode material with a chemical formula of Li 1.13 Mn 0.511 Ni 0.253 Co 0.096 Ta 0.005 Al 0.005 O2, which is a single crystal particle with a particle diameter of 3 μm, a surface spinel phase thickness of 4 nm, and a bulk phase doping layer thickness of 1 μm. The concentrations of active metals Ni, Co, and Mn gradually increase from the outside to the inside, and the concentrations of doping elements Ta and Al gradually decrease from the outside to the inside.

[0046] The preparation method is as follows:

[0047] (1) Taking the Ta doping amount as 0.5% and the Al doping amount as 0.5% as the target, lithium-rich positive electrode precursors (Mn 0.594 Ni 0.294 Co 0.112 CO3), tantalum ethoxide, 20 nm Al2O3, 100 ml of ethanol, and 100 ml of isopropanol were added into a mechanical fusion device and nitrogen was introduced, and the device was operated at a rotation speed of 7000 r / min for 5 min to obtain a mixed slurry;

[0048] (2) The mixed slurry was subjected to solid-liquid separation, washed with ethanol for 3 times, and vacuum dried at 80°C for 12 h to obtain a coated precursor;

[0049] (3) The coated precursor and lithium carbonate (molar ratio of 1:1.6) were added into a high-speed mixer and mixed at a high speed for 1 h, and the mixed material was placed into a muffle furnace, and calcined at a rate of 10°C / min to 500°C for 5 h, then calcined at a rate of 10°C / min to 950°C and kept for 12 h, and cooled to room temperature to obtain a lithium-rich positive electrode material Li 1.13 Mn 0.511 Ni 0.253 Co 0.096 Ta 0.005 Al 0.005 O2.

[0050] A lithium-rich positive electrode material Li 1.13 Mn 0.511 Ni 0.253 Co 0.096 Ta 0.005 Al 0.005The electrochemical performance of O2 coin cells was tested, and the results showed that its discharge specific capacity reached 273.8 mAh / g during cycling in a voltage range of 2 to 4.6 V and a current density of 250 mA / g, and the capacity retention rate was as high as 91.3% after 300 cycles.

[0051] Example 3

[0052] This embodiment provides a lithium-rich cathode material with the chemical formula Li. 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.0 1Mg 0.01 O2 consists of near-spherical aggregates with a diameter of 15 μm, a surface spinel phase thickness of 20 nm, and a bulk doped layer thickness of 5 μm. The concentrations of active metals Ni, Co, and Mn gradually increase from the outside to the inside, while the concentrations of dopants Ti, Al, and Mg gradually decrease from the outside to the inside.

[0053] The preparation method is as follows:

[0054] (1) With Ti doping of 1%, Al doping of 1%, and Mg doping of 1%, a lithium-rich precursor (Mn) with a particle size of 15 μm was weighed. 0.594 Ni 0.294 Co 0.112 (OH)2), tetrabutyl titanate, aluminum isopropoxide, 20 nm magnesium oxide, 50 ml ethanol and 100 ml isopropanol were added to the mechanical fusion device and nitrogen gas was introduced. The device was run at a speed of 5000 r / min for 15 min to obtain a mixed slurry.

[0055] (2) The mixed slurry was subjected to solid-liquid separation, washed three times with ethanol, and vacuum dried at 80°C for 12 hours to obtain the coated precursor.

[0056] (3) The coated precursor and lithium hydroxide (molar ratio 1:1.35) were added to a high-speed mixer and mixed at high speed for 1 hour. The mixed material was then placed in a muffle furnace and calcined at 600°C for 5 hours with air as the calcination atmosphere. Immediately afterwards, the temperature was increased to 900°C at a rate of 20°C / min and held for 10 hours. After cooling to room temperature, the material was washed three times to obtain the Ti-Al-Mg gradient doped modified lithium-rich cathode material Li. 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.01 Mg 0.01 O2.

[0057] A lithium-rich positive electrode material Li 1.13 Mn 0.49 9Ni 0.257 Co 0.093 Ti 0.01 Al 0.01 Mg 0.01 O2 was prepared by the same method as in Example 1. The electrochemical performance of the lithium-rich positive electrode material Li

[0058] Example 4

[0059] The present embodiment provides a lithium-rich positive electrode material with a chemical formula of Li 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.0 1Mg 0.01 O2, which is a spherical agglomerate particle with a particle diameter of 13 μm, a surface spinel phase thickness of 10 nm, and a bulk phase doping layer thickness of 300 nm. The concentrations of active metals Ni, Co, and Mn gradually increase from the outside to the inside, and the concentrations of doping elements Ti, Al, Mg, and Zr gradually decrease from the outside to the inside.

[0060] The preparation method is as follows:

[0061] (1) With a target Ti doping amount of 1.5%, an Al doping amount of 1.5%, a Mg doping amount of 1.5%, and a Zr doping amount of 1.5%, lithium-rich positive electrode precursor particles (Mn 0.594 Ni 0.294 Co 0.112 CO3), tetrabutyl titanate, aluminum isopropylate, 50 nm MgO, 100 nm ZrO2, 50 ml ethanol, and 100 ml isopropyl alcohol were added to a mechanical fusion device and nitrogen was introduced, and the device was operated at a rotation speed of 6000 r / min for 8 min to obtain a mixed slurry;

[0062] (3) The mixed slurry was subjected to solid-liquid separation, washed with ethanol three times, and vacuum dried at 80°C for 12 h to obtain a coated precursor;

[0063] (4) The coated precursor and lithium carbonate (molar ratio 1:1.7) were mixed in a high-speed mixer at high speed for 1 h. The mixed material was placed in a muffle furnace, and calcined at a rate of 8 ℃ / min to 550 ℃ for 5 h, then at a rate of 10 ℃ / min to 880 ℃ and kept for 12 h, cooled to room temperature, to obtain Ti-Al-Mg-Zr gradient-doped modified lithium-rich positive electrode material Li 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.01 Mg 0.01 O2.

[0064] The same method as in Example 1 was used to prepare a button-type half cell containing Ti-Al-Mg-Zr gradient-doped modified lithium-rich positive electrode material Li 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.01 Mg 0.01 O2. The electrochemical performance of the button-type half cell was tested, and the results showed that the discharge specific capacity of the button-type half cell was up to 145 mAh / g when cycled at a voltage range of 2.8-4.4 V and a current density of 180 mA / g, and the capacity retention rate was as high as 95.3% after 250 cycles.

[0065] Example 5

[0066] This example provides a lithium-rich positive electrode material with the chemical formula Li 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.0 1Zr 0.01 O2, which is a single-crystal particle with a particle diameter of 3 μm, a surface spinel phase thickness of 1 nm, and a bulk phase doping layer thickness of 200 nm. The concentrations of active metals Ni, Co, and Mn gradually increase from the outside to the inside, and the concentrations of doping elements Ti, Al, and Zr gradually decrease from the outside to the inside.

[0067] The preparation method is as follows:

[0068] (1) The lithium-rich positive electrode precursor (Mn 0.594 Ni 0.294 Co 0.112CO3), tetrabutyl titanate, aluminum isopropyl alcohol, 20 nm ZrO2, 10 ml deionized water and 100 ml isopropyl alcohol were added into a mechanical fusion device and nitrogen was introduced, and the device was operated at a rotation speed of 6000 r / min for 30 min to obtain a mixed slurry;

[0069] (3) The mixed slurry was subjected to solid-liquid separation, washed with deionized water for 3 times, and vacuum dried at 85℃ for 14 h to obtain a coated precursor;

[0070] (4) The coated precursor and lithium carbonate (molar ratio of 1:1.8) were mixed in a high-speed mixer for 1 h, and the mixed material was placed in a muffle furnace, first heated to 550℃ at a rate of 5℃ / min and calcined for 5 h, then heated to 970℃ at a rate of 10℃ / min and kept for 18 h, cooled to room temperature, then washed with deionized water for 3 times and dried at 100℃ to obtain a Ti-Al-Zr gradient doped modified single-crystal lithium-rich cathode material Li 1.13 Mn 0.499 Ni 0.257 Co 0.093 Ti 0.01 Al 0.01 Zr 0.01 O2.

[0071] A coin-type half cell containing the Ti-Al-Zr gradient doped modified lithium-rich cathode material Li 1.13 Mn 0.49 9Ni 0.257 Co 0.093 Ti 0.01 Al 0.01 Zr 0.01 O2was prepared by the same method as in Example 1, and its electrochemical performance was tested. The results showed that the discharge specific capacity of the coin-type half cell was up to 139 mAh / g when cycled at a voltage range of 2-4.3 V and a current density of 150 mA / g, and the capacity retention rate was as high as 99.6% after 200 cycles.

[0072] Comparative Example

[0073] The precursor was not coated, and the other experimental steps were carried out according to Example 1.

[0074] A coin-type half cell of an unmodified sample was prepared by the same method as in Example 1, and its electrochemical performance was tested. The results showed that the discharge specific capacity of the coin-type half cell was 286.8 mAh / g (as shown in the figure) when cycled at a voltage range of 2-4.8 V and a current density of 250 mA / g, and the capacity retention rate was only 85.8% (as shown in the figure) after 200 cycles, and the average voltage decay per cycle was 0.205 mV (as shown in the figure). Figure 5 Figure 6 Figure 7 ​​​

[0075] The above is only the preferred embodiment of the present application. It should be noted that for those skilled in the art, some adjustments can be made to the raw material ratio without departing from the principles of the present application, and these should also be considered within the scope of the present application.

Claims

1. A lithium-rich cathode material, characterized in that: Li 1+x TM 1-x-y D y O2; wherein TM is at least two of Ni, Co, Mn, D is at least two of Mg, Ti, Al, Zr, Nb, Ta doping elements, 0 < x < 0.4, 0 < y < 0.06; The lithium-rich cathode material is a single-crystal particle or a spherical agglomerate particle, and the particle has a spinel phase and a bulk phase from outside to inside, and the bulk phase is a layered phase with a "twin domain" feature. In the lithium-rich cathode material, the concentration of TM gradually increases from outside to inside, and the concentration of the doping element D gradually decreases from outside to inside. 2.The lithium-rich cathode material of claim 1, wherein: The particle size of the lithium-rich cathode material is 2-20 μm, the thickness of the spinel phase is 1-20 nm, and the thickness of the bulk phase doping layer is greater than or equal to 200 nm.

3. The method of producing a lithium-rich cathode material according to any one of claims 1 to 2, characterized in that, The method comprises the following steps: S1, according to the chemical formula of the lithium-rich cathode material, the lithium-rich precursor, the coating agent and the dispersant are weighed and added into a mechanical fusion device, and a protective gas is introduced for mechanical fusion coating to obtain a mixed slurry; S2, the mixed slurry is subjected to solid-liquid separation, washed with a dispersant or deionized water, and dried to obtain a coated precursor; S3, the coated precursor and a lithium source are uniformly mixed according to a molar ratio, and then subjected to high-temperature calcination in sections, and the target lithium-rich cathode material is obtained after cooling.

4. The method for preparing the lithium-rich cathode material according to claim 3, characterized in that: The lithium-rich precursor is a Ni-Co-Mn-based carbonate or a Ni-Co-Mn-based hydroxide.

5. The method for preparing the lithium-rich cathode material according to claim 4, characterized in that: The coating agent comprises a powder coating agent and an easily hydrolyzable salt coating agent, wherein the powder coating agent is an oxide or a hydroxide; the easily hydrolyzable salt coating agent is at least one of tantalum ethoxide, tantalum pentachloride, niobium ethoxide, aluminum isopropylate, aluminum sec-butoxide, tetrabutyl titanate, titanium isopropoxide and titanium tetrachloride.

6. The method for preparing the lithium-rich cathode material according to claim 5, characterized in that: The oxide is at least one of magnesium oxide, aluminum oxide, niobium pentoxide and tantalum pentoxide with a particle size of 5-100 nm; and the hydroxide is at least one of magnesium hydroxide, aluminum hydroxide and zirconium hydroxide.

7. The method for preparing the lithium-rich cathode material according to claim 4, characterized in that: The dispersant is at least one of water, methanol, ethanol, ethylene glycol, isopropyl alcohol and polyvinyl alcohol solution.

8. The method for preparing the lithium-rich cathode material according to claim 4, characterized in that: The lithium source is lithium carbonate or lithium hydroxide.

9. The method for preparing the lithium-rich cathode material according to claim 4, characterized in that, The specific process of the high-temperature calcination in sections is as follows: first, the temperature is increased to 400-600 ℃ at a rate of 5-20 ℃ / min, and calcined for 2-8 h; then, the temperature is increased to 800-1000 ℃ at a rate of 5-20 ℃ / min, and calcined for 8-20 h.

10. A lithium-ion battery, characterized by: The lithium ion battery comprises the lithium-rich cathode material according to any one of claims 1-2 or the lithium-rich cathode material prepared by the preparation method according to any one of claims 4-9.

Citation Information

Cited By

  • Modified cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN121894717A

  • A modified cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof

    CN121894717B